The Effect Of Tax Avoidance On Firm Value With Earnings Management As A Mediation Variable - Dinda Olanda; Fenny Marietza (UNIVED Press, 2024)
The objective of this research is to determine the effect of tax avoidance on firm value, using earnings management as a mediating variable. This research filled an empirical vacuum left by earlier research that used agency theory and signal theory to reexamine the effect of tax avoidance on firm value. This research was carried out to fill up an empirical gap in earlier research that sought to use agency theory and signal theory to reexamine the effect of tax avoidance on firm value. This research is innovative in that it looks at earnings management as a mediator between tax avoidance and firm value. This research makes use of secondary data and a quantitative methodology. Manufacturing enterprises registered on the Indonesia Stock Exchange (BEI) for the 2018–2022 period make up the research population. A total of 185 observations from 37 firm's in this research sample satisfied the criteria. The results of this research show that tax avoidance has an effect on firm value, earnings management has no effect on firm value, and earnings management cannot mediate the effect of tax avoidance on firm value.